Consumer behavior during the pandemic Covid 19 - Chu, Yi Ching; Abu Seman, Noor Aslinda; Harun, Amran (Penerbit UTHM, 2022)
An outbreak of Covid-19 is not simply a global pandemic and public health crisis only. The pandemic has affected the global economy and financial markets. According to Sheth (2020), the Covid-19 pandemic and lockdown and the social distancing mandates have disrupted consumer buying behavior, especially at shopping. Many industries have undoubtedly been impacted, particularly service and industrial activities, which have been stopped to the point of insolvency. This is because much of the globe has imposed quarantine restrictions to contain the pandemic's spread, advising residents to stay at home and only go to acquire the necessities. Many customers' options for shopping are limited as a result of the lockdown and social distancing. This scenario has undoubtedly had an impact on consumer purchasing patterns. As a result, the shutdown significantly influences consumer behaviour, personal views, individual and household experiences, and traits.